The Validation And Application Of Bahasa Malaysia Gender Equitable Men (Gem) Scale: An Assessment Of Equitable And Inequitable Gender Norms Among Male Students Of A Malaysian University - Sukumaran, Vasumathy (2013)
One of the concerns raised at various international conferences is the link between gender inequality and gender inequity, and sexual and reproductive health issues. Past research findings have shown that inequitable gender norms negatively affect sexual and reproductive health behaviours, and are also linked to all forms of violence against women by men. This indicates the importance of transforming norms in the society for a more egalitarian relationship between men and women, and the importance of having tools to measure changes in gender norms. The GEM Scale, developed by the Horizons and Institute Promundo, is designed to identify and measure the prevailing gender norms in the community. The objectives of the current study are to validate the Bahasa Malaysia GEM Scale, to use it to identify the prevailing gender norms, and to measure the level of gender norms among male students of a university in Malaysia. The first phase involved translating the scale into Bahasa Malaysia, adapting and then validating it among 215 university male students. The second phase was the application of the validated Bahasa GEM Scale. Data were collected from 661 male students from a university in northern Malaysia. The validation results showed that the Bahasa Malaysia GEM Scale is valid with the Cronbach Alpha value 0.79, and can be used in Malaysia.